Em busca do fiel da balança de Têmis: análise econômica do direito e ponderação - Cavalcanti, Mariana Oliveira de Melo (2019)
Starting from the transformations engendered by neoconstitutionalism in contemporary juridical hermeneutics, the present dissertation addresses the extension of the constitutional jurisdiction and the challenges to the traditional process of balancing. Comparing the critiques with the theoretical assumptions of the balancing formula - pertinent to the third sub-principle of proportionality, which occurs in the strict sense -, it seeks to make explicit the efforts directed at a greater methodological ordering of the balancing process, in order to give it greater objectivity. In the meantime, it examines the possibility of the economic tool to guide legal decisions, analyzing the feasibility of the management of the Economic Analysis of Law as a way of subsidizing the balancing mechanism, analyzing the doctrinal, legal and jurisprudential panorama on the subject.